The Global Dimension of the “Populist Wave”: Possibilities for Differentiated Analysis - Sergey A. Shein; Artem A. Alikin (RUDN Journal of Political Science, 2022)
The article attempts to reveal if it is possible to make a differentiated analysis of the global dimension of populism by systematizing foreign (mainly) and domestic studies. This allowed us to correlate the theoretical and comparative developments of research on populism, on the one hand, and the relevant, traditional problem areas of the international relations theory. This approach helped us to demonstrate both the existing and potential possibilities for a differentiated analysis of the global aspects of populism. The scientific novelty of the article lies in determining the possibilities of the academic field for the analysis of the foreign policy effects of populism. As a result of the study, the author concluded that the foreign policy positions and policies of populists derive from domestic politics and their opposition to traditional elites. Structural pressure (pressure of the international environment) and the adoption of the rules of the game after coming to power, even if the anti-elite discourse is maintained, make attempts to typify and classify populist foreign policy positions extremely complex and often unproductive.